Analisis Preliminery Research Phase Menggunakan Model Pengembangan Plomp Sebagai Dasar Pengembangan Modul Belajar dan Pembelajaran Pendidikan Biologi Bermuatan Hasil Riset Untuk Mahasiswa - Nurul Fauziah; Iffa Ichwani Putri; Oktariani Oktariani (Universitas Lampung, 2021)
The purpose of this study is to describe the preliminery research phase data obtained as a basis for the development of learning and learning modules containing research results that will be developed later. The development model used in this study is the Plomp model which has been carried out until the initial investigation data stage. Preliminary investigation data revealed some initial findings including; analyzing the Semester Learning Plan (RPS), interviews with learning and learning lecturers in the Biology Education Study Program FKIP Riau Islamic University, student questionnaire problems in conducting learning and learning lectures, student needs questionnaire in learning and learning lectures, and analysis of learning and learning modules used in learning and learning teaching materials previously in learning and learning lectures. The results revealed in the analysis of the Semester Learning Plan (RPS) there were thirteen topics in learning and learning. The results of interviews conducted with lecturers in learning and learning courses also revealed obstacles in the implementation of learning and learning lectures, one of which was the lack of student references to study learning and learning. Student problem questionnaire revealed that students do not yet have a learning and learning module with a percentage of 13.71%. Student needs questionnaire revealed that students strongly agree the need to develop learning and learning modules containing research results with a percentage of 100%. The learning and learning module that has been used in the learning process does not meet the standards of the Ministry of Research, Technology, and Higher Education Directorate General of Learning and Student Affairs Directorate of Learning in 2017. The conclusion of this study is the need to develop learning and learning modules containing research results for biology students to help the lecture process in the classroom.Tujuan penelitian ini adalah untuk mendeskripsikan data preliminery research phase yang didapatkan sebagai dasar pengembangan modul belajar dan pembelajaran bermuatan hasil riset yang akan dikembangkan nantinya. Model pengembangan yang digunakan dalam penelitian ini adalah model Plomp yang telah dilakukan sampai tahap data investigasi awal. Instrumen pengumpulan data menggunakan wawancara, observasi dan angket. Hasil penelitian mengungkapkan pada analisis Rencana Pembelajaran Semester (RPS) terdapat 13 topik dalam perkuliahan belajar dan pembelajaran. Angket permasalahan mahasiswa mengungkapkan mahasiswa belum memiliki modul bioteknologi dengan presentase 13,71%. Angket kebutuhan mahasiswa mengungkapkan mahasiswa sangat setuju perlu dikembangkannya modul belajar dan pembelajaran bermuatan hasil riset dengan presentase 100%. Modul belajar dan pembelajaran yang telah digunakan dalam proses pembelajaran belum memenuhi standar dari Kementrian Riset, Teknologi, dan Pendidikan Tinggi Direktorat Jenderal Pembelajaran dan Kemahasiswaan Direktorat Pembelajaran tahun 2017. Kata kunci: hasil riset, modul pembelajaran, studi pendahuluanDOI: http://dx.doi.org/10.23960/jbt.v9i3.23072